Correlation amongst Indoor Air Quality, Ventilation and Carbon Dioxide - Sireesha, N. L. (Journal of Scientific Research, 2017)
The calculation of carbon dioxide (CO2) intensities can be employed to see the quality of indoor air and ventilation. The studies undertaken till date have been distorted. The current study summaries the association amongst carbon dioxide and building air quality and ventilation, with carbon dioxide being the marker to evaluate air quality and ventilation performance. High carbon dioxide intensities may show insufficient ventilation per occupant and high indoor contaminants intensities, resulting in the Sick Building Syndrome (SBI) Symptoms. The researcher assessed the literature related to indoor air quality (IAQ), ventilation, and building-linked health issues in schools linked to CO2 discharges and recognised general indicated building-linked well-being signs found in schools. A high rise in the ventilation rate or enhancement in ventilation efficacy and/or indoor contaminant source regulation would be anticipated to reduce the occurrence of chosen signs to its optimum.